Nuclear genome size determination of Christia Vespertilionis via flow cytometry - Midin, Mohd Razik; Fikri, Muhammad Irfan; Zailani, Siti Sarah (Sciendo, 2020)
Christia vespertilionis (butterfly wing plant) is an ornamental plant originated from South East Asia with reported usage in traditional medicine practice and potential as an anticancer and antitumor. This research aims to estimate the genome size of C. vespertilionis via flow cytometry (FCM) method. The research was conducted with the optimisation of nuclear suspension preparation followed by the genome size estimation. Two chopping techniques [manual chopping (MC) and BDTM Medimachine (MM)] and two lysis buffers (Otto and LBO1) were tested. Otto buffer with manual chopping was found to be the most suitable method, generated fine DNA peak with minimum debris background, and coefficient of variation (CV) value less than 3%. Five replicates of the FCM analysis were made for the genome size determination. The estimated genome size of C. vespertilionis was found to be 3.22 pg by using Glycine max cv. Polanka (2C=2.5pg) as an external reference standard. Further comparison with other Christia species was not possible due to